SINTESIS FOTOKATALIS TIO2/CNCS UNTUK MENGKONVERSIKAN CO2 MENJADI SOLAR FUEL: UJI AKTIVITAS DAN STABILITAS - Boron Alfisyahri Budima, Mikail
CO2 is one of the gas emission that contributes toward greenhouse gas effect. CO2 emission from energy in Indonesia reach 261,89 million tons in 2015. Now, CO2 emission from industry is always flowed into the atmosphere without any pretreatment. CO2 conversion into solar fuel via photoreduction is one of the interesting solution because it produced high value product. The development of photoreduction now is using titanium dioxide (TiO2) as photocatalyst. But, using pure TiO2 can decrease the catalytic activity of it because it agglomerated. Agglomeration can be prevented by using a support. Cellulose Nanocrystals (CNCs) are an advanced biomaterial that can be used as catalyst support. CNCs are a crystal nanoparticles made of cellulose with diameter of 3-50 nm and length of 100-200 nm. CNCs have a high surface area (150-250 m2/g). CNCs usage as support can disperse TiO2 on CNCs surface and increase the surface area of TiO2. This research aims to synthesize TiO2/CNCs nanocatalyst and reviewing the activity and stability of nanocatalyst in CO2 photoreduction reaction. This research consist of several experimental steps which include CNCs synthesis using APS oxidation, TiO2/CNCs nanocatalyst synthesis using sol-gel method with TTIP as the precursor, TiO2/CNCs nanocatalyst characterization using XRD, TEM, and PSA, also activity test of TiO2/CNCs photocatalyst in CO2 photoreduction process into solar fuel. TiO2/CNCs nanocatalyst synthesis process consist of several variations. The precursor volume variations are 1, 2, 3, and 4 ml in 100 ml solution. Aging time variation are 12, 24, 36, and 48 hours. XRD analysis shows CNCs crystallinity is 71,8% but the formed TiO2 is still in amorphous state. CNCs have rod like and spherical shape. PSA analysis of TiO2/CNCs shows that 36% have average diameter of 48,5 mm and 64% have average diameter of 269,7 mm. TEM analysis shows some formed TiO2 are already on CNCs.